Neointimal macrophages colocalize with extracellular matrix gene expression in human atherosclerotic pulmonary arteries. - Liptay, M J (1993)
Vascular remodeling in adult atherosclerotic pulmonary arteries is characterized by discrete areas of neointimal extracellular matrix gene expression, suggesting regulation by local factors. Though the factors responsible for inducing matrix gene expression in atherosclerotic lesions are largely unknown, several observations suggest macrophages may be a focal source of those factors. Immunohistochemistry confirmed the presence of macrophages in the neointima of atherosclerotic elastic pulmonary arteries from patients with unexplained pulmonary hypertension. Areas of neointima containing dense clusters of macrophages were separated by sparsely populated areas. Foamy macrophages resided more deeply within the neointima than nonfoamy macrophages, which were found more often subjacent to the endothelium or within the lumenal one-third of the neointima. Combined immunohistochemistry-in situ hybridization indicated neointimal fibronectin and type I procollagen gene expression was intimately associated only with nonfoamy neointimal macrophages. These observations suggest that: (a) nonfoamy neointimal macrophages participate in the local regulation of extracellular matrix gene expression in atherosclerotic pulmonary arteries; (b) foamy macrophages, which are not associated with matrix gene expression, have undergone modulation of their secretory phenotype.